Kegagalan Elektoral PPP Dalam Pemilu 2024 : Analisis Propaganda Politik Dan Pemasaran Berdasarkan Citra Partai Dan Demografi Pemilih - Kusnadi, Kusnadi; Arifin, Miftahol; Syahrullah, Ahmad (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
The United Development Party (PPP), as one of the oldest Islamic parties in Indonesia, experienced electoral failure in the 2024 Election by failing to pass the 4% parliamentary threshold, only winning 3.87% of the national vote. This study aims to analyze the factors of PPP's failure by focusing on two main aspects: political propaganda and image marketing (political branding). A qualitative approach with case studies is used to examine the mismatch between PPP's traditional image and the demographic characteristics of young voters who dominate the election. The findings show that PPP's failure was triggered by the party's inability to adapt its political communication strategy to social and technological changes. PPP still relies on classical religious symbolism and conventional campaigns that are ineffective in reaching millennial and Gen Z voters who are more critical, pragmatic, and digital-oriented. Weak digital marketing, the absence of young figures, internal conflicts, and the lack of synchronization of ideological narratives with contemporary issues such as the digital economy and social justice have also worsened the party's political performance. The conclusion of this study emphasizes the need for structural reform, ideological rebranding, and adaptation of communication strategies to restore PPP's political relevance amidst the ever-changing landscape of digital democracy.